Contextual and interventional factors that affect the implementation of the World Health Organisation surgical safety checklist in the operating theatres of a designated private hospital - Van Wyk, Neltjie C. (University of Pretoria, 2023)
Dissertation (MA (Nursing Science))--University of Pretoria, 2022.